E^2x -2e^x -8=0 => e<span>^(2x) -2e^x -8=0
Temporarily replace e^x with y.
Then (y)^2 - 2y - 8 = 0. Factors are (y-4) and (y+2).
Roots are y = 4 and y= -2.
Now remembering that we temporarily replaced e^x with y, we let
y=4 = e^x. We need to solve for x. Taking the natural log of both sides, we get:
ln 4 = x (answer)
We have to discard the other root (y= -2), because we cannot take the ln of a negative number.
</span>
Answer:
m<1 = 79°
Step-by-step explanation:
12x + 19 + 22x - 9 = 180
add the numbers
34x + 10 =180
minus 10
34x = 170
divide by 34
x = 5
plug 5 into the equation of angle 1
12(5) + 19 =
79
Answer:
3/4 gallons of juice
Step-by-step explanation:
Katie bought 2 one-gallon bottles for a party.
2 one-gallon bottles = 2-gallon bottles of juice
We are told that:
Her guest drank 5/4 gallons of juice.
The fraction of juice leftover is calculated as:
2 gallons of juice - 5/4 gallons of juice
2 - 5/4
Lowest Common Denominator = 4
2/1 - 5/4
= 8 - 5/4
= 3/4 gallons of juice
Therefore, the fraction of juice leftover is 3/4 gallons of juice
Well a half cup is 2/4 and if the serving size is 3/4 there is only 66.66% of the serving size needed hope this helps!
Answer: it’s not an even number it 6.6 repeating so if round up and say 7 bags
Step-by-step explanation: